A Case of Candidemia after Long-term Presence of Urethral Foreign Bodies. (2021) - Nagata, Jun; Kawasaki, Takeshi; Iesato, Ken; Sugiura, Toshihiko; Yamauchi, Keita; Tsuyusaki, Junichi; Fujimura, Masaaki; Kuroda, Fuminobu; Mikami, Kazuo; Dudek, Steven M.; Tanabe, Nobuhiro
Abstract: A 52-year-old man presented to our hospital complaining of general malaise, cough, and fever. Total body computed tomography revealed scattered pneumonia and urethral foreign bodies that had been inserted during adolescence. Candida glabrata was detected in blood and urine cultures. Based on these findings, the patient was diagnosed with candidemia that developed due to Candida urinary tract infection, complicated by septic pulmonary embolism and severe diabetes mellitus. Candidemia likely persisted despite the initiation of intravenous antifungal therapy and control of blood sugar level. Therefore, surgical removal of the urethral foreign bodies was performed, which resulted in resolution of the patient's symptoms. Herein, we report a rare case of candidemia complicated by Candida urinary tract infection that developed due to the long-term presence of urethral foreign bodies. A multidisciplinary therapeutic approach, including surgical removal of the infected foreign bodies, is effective in such cases. This case indicates that long-term presence of foreign bodies and acquired immune dysfunction can be risk factors for candidemia. Therefore, detailed history should be obtained and systemic examination should be performed to identify the complicating risk factors on diagnosis of candidemia.